Psychological issues in acquired facial trauma - Avinash De Sousa (Indian Journal of Plastic Surgery)
The face is a vital component of one's personality and body image. There are a vast number of variables that influence recovery and rehabilitation from acquired facial trauma many of which are psychological in nature. The present paper presents the various psychological issues one comes across in facial trauma patients. These may range from body image issues to post-traumatic stress disorder symptoms accompanied by anxiety and depression. Issues related to facial and body image affecting social life and general quality of life are vital and the plastic surgeon should be aware of such issues and competent to deal with them in patients and families.